2014
DOI: 10.3390/ijms150711973
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 Inhibits NSCLC Cell Growth and Metastasis by Targeting Limk1

Abstract: MicroRNAs (miRNAs) have essential roles in carcinogenesis and tumor progression. Here, we investigated the roles and mechanisms of miR-143 in non-small cell lung cancer (NSCLC). miR-143 was significantly decreased in NSCLC tissues and cell lines. Overexpression of miR-143 suppressed NSCLC cell proliferation, induced apoptosis, and inhibited migration and invasion in vitro. Integrated analysis identified LIM domain kinase 1 (Limk1) as a direct and functional target of miR-143. Overexpression of Limk1 attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 30 publications
3
27
0
1
Order By: Relevance
“…5A). These data suggest that LIMK1 is a likely target of miR-143 in these As-CSC cells, consistent with reports of miR-143 directly targeting LIMK1in non-small cell lung cancer (NSCLC) (Xia et al 2014). To ensure that the decrease in LIMK1 protein levels is not caused by other upstream regulators of LIMK1 such as Rac, ROCK and PAK1 (Manetti 2012), we examined the protein levels of these regulators.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…5A). These data suggest that LIMK1 is a likely target of miR-143 in these As-CSC cells, consistent with reports of miR-143 directly targeting LIMK1in non-small cell lung cancer (NSCLC) (Xia et al 2014). To ensure that the decrease in LIMK1 protein levels is not caused by other upstream regulators of LIMK1 such as Rac, ROCK and PAK1 (Manetti 2012), we examined the protein levels of these regulators.…”
Section: Resultssupporting
confidence: 90%
“…These data are consistent with other reports showing that miR-143 restoration decreased the proliferation of the prostate cancer cell lines DU145, PC3, LNCaP and C4-2 enhancing their sensitivity to docetaxel (Xu et al 2011), and abrogating tumor growth in mice (Clape et al 2009). Similarly, miR-143 is downregulated in various cancer cells including leukemia cells (Shen et al 2014), non-small cell lung cancer (NSCLC) (Xia et al 2014), cervical cancer (Lipeng et al 2012), and melanoma cells (Li et al 2014). Restoration of miR-143 in these cancer cells inhibited cell proliferation and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs play critical roles in tumorigenesis, tumor cell proliferation, migration, invasion, metastasis and angiogenesis (Iuliano et al 2013;Di Leva et al 2014). A large number of microRNAs have been aberrantly found in NSCLC, and many of them contribute to NSCLC development and progression (Chen et al 2013b;Xia et al 2014b;Xia et al 2014a). The role of microRNAs may be altered between NSCLC (Hu et al 2008) and SCLC (Liu and Chen 2011), thus we only focus on NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of mRNAs in the MIR143HG-associated PPI module in secretory LUSC were all positively correlated with MIR143HG, and these mRNAs were enriched in functions related to extracellular matrix organization and cell adhesion (Figure S10). Many studies have reported that the overexpression of miR-143 inhibited cell migration and invasion3738. Hence, MIR143HG and miR-143 might be involved in similar biological processes via different regulatory mechanisms, whereby MIR143HG activates targets and miR-143 represses targets.…”
Section: Resultsmentioning
confidence: 99%